Słoweniec jako wieczny student i nie tylko – wycinek z polsko-słoweńskich badań ankietowych - Wacławek, Maria; Wtorkowska, Maria (Postscriptum Polonistyczne, 2020)
The educational system in a given country largely influences the process of shaping of the students’ identity. The text is a study on an excerpt from material which is part of research reconstructing the linguistic and cultural image of Poles and of Slovenians. An analysis of the operational categories of the linguistic image of the world is a valuable source of knowledge about the stereotypical image of the country and of its representatives, reflecting the subjective point of view of respondents. A binary model emerges clearly, with a positive – negative (unambitious) attitude of Slovenians towards science and education. The comparison of the auto- and heterostereotypical approach, in our case the Slovenian one with the Polish one (respondents who had had contact with Slovenians), yields a broader picture of the studied aspect.